Investigation of the relationship between anosmia in patients with COVID-19 and allergic rhinitis and eosinophil levels - Asude Unal; Ayse Cecen; Dursun Mehmet Mehel; Semih Van (Medicine Science, 2023)
Anosmia is a common symptom of COVID-19 infection. In our study, we aimed to investigate the relationship between allergic rhinitis and eosinophil levels in patients who developed anosmia after COVID-19 infection. Patients who had experienced COVID-19 infection and subsequently developed anosmia were included in the study group, while those who had experienced COVID-19 infection but did not develop anosmia were included in the control group. The patients' allergy histories and eosinophil levels were retrospectively analyzed. Our study revealed a significant difference in eosinophil levels between patients with and without anosmia (p [Med-Science 2023; 12(3.000): 685-8]